2000
DOI: 10.1086/312662
|View full text |Cite
|
Sign up to set email alerts
|

[ITAL]Chandra[/ITAL] X-Ray Observations of the Hydra A Cluster: An Interaction between the Radio Source and the X-Ray–emitting Gas

Abstract: We present Chandra X-ray observations of the Hydra A cluster of galaxies, and we report the discovery of structure in the central 80 kpc of the cluster's X-ray-emitting gas. The most remarkable structures are depressions in the X-ray surface brightness, approximately 25-35 kpc in diameter, that are coincident with Hydra A's radio lobes. The depressions are nearly devoid of X-ray-emitting gas, and there is no evidence for shock-heated gas surrounding the radio lobes. We suggest that the gas within the surface b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
496
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 595 publications
(523 citation statements)
references
References 13 publications
26
496
1
Order By: Relevance
“…In contrast, the radio morphology does not appear correlated with the X-ray emission. An anticorrelation between X-ray and radio morphology has been seen in some nearby clusters of galaxies (McNamara et al 2000), but these data do not clearly show this effect.…”
Section: Optical and Radio Comparisonsmentioning
confidence: 73%
“…In contrast, the radio morphology does not appear correlated with the X-ray emission. An anticorrelation between X-ray and radio morphology has been seen in some nearby clusters of galaxies (McNamara et al 2000), but these data do not clearly show this effect.…”
Section: Optical and Radio Comparisonsmentioning
confidence: 73%
“…The X-ray filament coincides with an emission line filament observed in Hα+NII (Cowie et al 1983). In Hydra A McNamara et al (2000) observed a flattened excess X-ray emission structure which is coincident with a gaseous star-forming disk with an estimated star formation rate between 1 and 15 M yr −1 (depending on the duration of the assumed star burst ∼10 9 or 10 8 yr, respectively, McNamara et al 2000). Also in A1835 an excess emission region close to the center and inhomogeneities are observed.…”
Section: Evidence For Inhomogeneities and Mass Deposition In X-ray Immentioning
confidence: 95%
“…Therefore, this activity can have a repeated impact on the AGN host galaxy and its environment, starting from the initial phase of the radio source's life (O'Dea 2002) on to its later stages (McNamara et al 2000). The morphology of a (recurrent) radio source can vary significantly (see e.g.…”
Section: Introductionmentioning
confidence: 99%